The North Line Jakarta Lrt: Operating System And Risk Analysis - Purnomo, Cahyo; Jayady, Arman (International Journal Labs, 2023)
The North line Jakarta LRT is one of the light rail transportation modes implemented to address the complex traffic issues in DKI Jakarta, Indonesia. Initial studies indicate that the existing headway and travel time are perceived as ineffective by users. This study aims to examine the effective headway in operating the North line Jakarta LRT and identify associated risks and their mitigation. The research employed survey methods through questionnaires, interviews, direct observations, and collected secondary data and documentation related to the North line Jakarta LRT. The analysis results revealed that passengers prefer a waiting time of 5 minutes during peak hours at 05:30-08:30 AM and 04:00-07:00 PM. A comprehensive risk analysis was also carried out using the interview method with open questions. This process identifies 14 potential risks associated with proposed changes to operating system patterns. A series of action plans have also been designed to effectively mitigate the identified risks.